2013
DOI: 10.1039/c3nr00517h
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 coated Au/Ag nanorods with enhanced photocatalytic activity under visible light irradiation

Abstract: A facile method was used to prepare uniform Au NR/TiO2 and Au/Ag NR/TiO2 core-shell composite nanoparticles. Au/Ag NR/TiO2 nanoparticles were found to display significantly enhanced visible light photo-catalytic activity compared to Au NR/TiO2 and the commercially available TiO2 nanoparticles. The enhancement mechanism was ascribed to injection of hot electrons of photo-excited Au/Ag NRs to TiO2, which was confirmed by 633 nm laser induced reduction of silver ions on the surface of Au/Ag NR/TiO2 composite nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
111
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(120 citation statements)
references
References 32 publications
6
111
0
3
Order By: Relevance
“…It has been demonstrated that Au or Au/Ag NRs enhance the photocatalytic activity of TiO 2 . A reasonable mechanism beyond the enhanced photocatalytic dye degradation is reported in Figure 8 [67].…”
Section: Water Remediationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that Au or Au/Ag NRs enhance the photocatalytic activity of TiO 2 . A reasonable mechanism beyond the enhanced photocatalytic dye degradation is reported in Figure 8 [67].…”
Section: Water Remediationmentioning
confidence: 99%
“…Moreover, noble metal nanoparticles can store photogenerated electrons, thus promoting charge separation in semiconductor-metal composite systems [66,67]. Several other factors may also affect photocatalytic efficiency, e.g., the surface properties, the particle size of the catalysts their morphology, and the composition and organization of the metal and TiO 2 [68].…”
Section: Tio2/plasmonic Material-based Hybrid Nanocrystalsmentioning
confidence: 99%
“…The effective utilization of the visible light (50% of solar spectrum) is main aim of study conducted by many research teams. A numerous modifi cation techniques, which seem to be promising for TiO 2 band-gap narrowing and shift the light absorption capacity towards visible wavelengths have been proposed [14][15][16] . The titania modifi ed with noble metals (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…ZnO, WO 3 , SiO 2 , CrO) and non-metals e.g. S, C, N are most often investigated photocatalysts [16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…Due to diverse structures and properties, the core-shell nanoparticles have wide applications in various fields such as surface-enhanced Raman scattering, photonic crystals, catalysis, nano-electronic devices, and biochemical sensor [1]- [7].Among the various core-shell nanoparticles, the fabrication of inorganic nanoparticles coated with the shell of polymers has attracted increasing attention as new materials because of their novel mechanical, electrical, and optical properties [8]- [9]. Characteristics of the hybrid colloids can be adjusted through the functionality of polymer moieties.…”
Section: Introductionmentioning
confidence: 99%